The effect of phosphorus addition on the age-hardening of Cu-Ni-Ti alloy - Lina Zhang; Xiangqin Zhao; Jiaqing Lai; Yihong Tian; Jianbo Zhang (Materials Research Express)
The effects of P addition on the microstructure and properties of a Cu-Ni-Ti alloy were investigated. The relationship between evolution of precipitates and hardness, electrical conductivity and softening temperature was established. The results showed that P addition increases the hardness and electrical conductivity, while also possessing good softening resistance. After 90% hot rolling and 500 °C aging, the Cu-Ni-Ti-P alloy reaches its maximum hardness and electrical conductivity of 165 HV and 57.2%IACS. Furthermore, the softening temperature of Cu-Ni-Ti-P alloy reaches 720 °C. The addition of P promotes the precipitation of Ni atoms from the Cu matrix, reduces the concentration of solute atoms, and as a result, increases the electrical conductivity of the alloy. Furthermore, the formation of the Ni _3 P phase further enhances the hardness of the alloy. The P solute atoms dissolved in the matrix and the nano-scale Ni _3 P phase form, which may be one reason for the increase in hardness due to precipitation strengthening.